Peran Pemimpin Tradisional dalam Pengelolaan Wilayah Laut (Kasus Desa Endokisi) - Masyhuri, Imron (Jurnal Masyarakat dan Budaya, 2000)
There are two traditional leaders in Endokisi, i.e. Ondoafi and Dewan Adat. Ondoafi is a head of ethnic, and Dewan Adat is a coordinating board between ondoajies, religion leader (church leader) and formal leader (Kepala Desa). The traditional leader have a great role to manage marine ecology in Endokisi. They decide on regulations about the system of marine resources exploitation, allowance process for exploitation, and decide on sanctions for the collision of regulation for marine area management. Regulations about the system of marine resources exploitation is not only related to the claim of marine area ownership and the rule of using marine ecology, but is also related with the use of non traditional exploitation gears and the kinds of marine resources prohibited to be caught. Related with this, regulations also decide that the allowance process should be done by fisherman who exploitate marine resources in that area, and decide on sanctions for the collision. To decide a rule in marine area management, many ondoafies meet and discuss with church leadesr and Kepala Desa. The task of chruch leader and kepala Desa are to give inputs and considerations for ondoafies about marine ecology rules that will be decided Based on those considerations ondoafies will decide wether the rules will be applied or not. So a rule should be based on the agreement between ondoafi and Dewan Adat, to give permission for other people to exploitate marine resources in the marine area of Endokisi, deciding on the allowance given by the ondoafi owner of marine area, by agreement of his people. Ondoafi provide information about his desition to Dewan Adat, and Dewan Adat provide information to the owner of the resources to be exploitated in that area, via kepala Desa. To determinion sanctions for the violater of regulations of, three elements of Dewan Adat are discussed to decide the kind of sanction will be done.